Simulation and Analysis of 3 D Transient Leakage Magnetic Field and Electromotive Force of Power Transformer - MU Long; CHEN Bo-gen; CAI Feng; WU Li-ming; DU Guo-an; lAN Sheng (Journal of Harbin University of Science and Technology)
In order to analyze the transient magnetic field and transient electrodynamic characteristics of transformer windings under shorL-circuit impact, according to the Lheo1-y of leakage magnetic field of transformer windings and the principle of calculation of short-circuit electrodynamics, using the finite element analysis software for calculating electromagnetic fields, a SSZl 1 - 50000/110 the three-winding power n·ansfo1mer is the research object, Lhe simulation model and short-circuit calculation equation of the transformer winding are established, and the simulation analysis of the transient leakage magnetic field and transient short-circuit electromotive force of the transformer is c打ried out. When the medium-voltage side winding of the transformer high-medium operation mode has a ground shmt-circuit fault, the transient leakage magnetic field of the winding and the disn-ibution law of the axial and radial transienl short-circuit electromotive force of the winding are calculated. The simulation results show that during the short-circuit process of the winding, the leakage magnetic field and the electromotive force distribution ru·e related to time and space, and all appear at the maximum value at t = 0. 01 s. At any time, the axial magnetic induction intensity is small on both sides and large in the middle; Lhe radial magnetic induction intensity between the medium-voltage and high-voltage windings is approximately "A" shaped. The distribution law of the radial electrodynamic direction of the \vindings on the inner side of the iron core ,vindow and the outer side of the iron core window is different The axial electromotive force of the winding is approximately symmeb-ically distributed in the center, and the elecb·omotive force on both sides is the largest, and the smallest is near the middle of the winding. This study provides a reference for preventing transformer winding defo1mation and improving design.